Facile hydrothermal synthesis of mesoporous WO3 /KIT-6 nanocomposite depicting great humidity sensitive properties. (7th June 2022) - Jakhar, Shivani; Duhan, Surender; Nain, Sonia
ABSTRACT: The present work deals with the synthesis and characterisation of a hybrid nanocomposite, WO3 -doped KIT-6, encompassing mesoporous characteristics, using novel hydrothermal practice with great humidity detection applications. The synthesised mesoporous hybrid nanocomposite having ordered Ia3d arrangement of the framework was investigated using N2 adsorption–desorption plots revealing significant surface area and pore volume. Furthermore, for the examination of structural insights, the sensing material was characterised using 'powder X-ray diffraction curves (XRD), transmission electron microscopy (TEM) visuals, scanning electron microscopy (SEM) imageries and energy dispersive X-ray analysis (EDXA)' data, unveiling Ia3d symmetry of mesoporous KIT-6. Furthermore, the humidity sensing data investigation of WO3 loaded in KIT-6 nanocomposite illustrates the relatively inconsiderate hysteresis values, magnificent stability of the sensing material with varying humidity content in the range of 11–98% relative humidity (RH) and a swift response/recovery time of 21 s and 24 s, respectively, depicting instantaneous recorded sensitivity towards varying humidity atmospheric levels. The presented work demonstrates the hydrothermal synthesis of a hybrid nanocomposite having ordered mesoporous cubic Ia3d geometry with considerable liability to consider as a sensing material in the assembly of advanced RH sensor with enhanced humidity sensitive properties.